Murder on Mistletoe Lane [large type] - McKenna, Clara (McKenna, Clara. Stella and Lyndy mystery., 2023)
American heiress Stella Kendrick and her husband, British aristocrat Viscount "Lyndy" Lyndhurst, prepare to celebrate their first Christmas together as newlyweds in Clara McKenna's latest historical mystery set in England's New Forest region at the turn of the 20th century...